Shrinath Automobiles Shop: An Application for Inventory Management System - Bhandare, Prashant; Sirsat, Harshvrdhan; Lokhande, Om (International Journal of Computer Sciences and Engineering, 2025)
The main focus of this project is the creation of an Inventory Management System (IMS), conceived to improve the inventory management of businesses of all sizes. It includes key features such as stock level tracking in real-time, automatic reorder notification generation, and detailed reporting tools. The IMS, with a friendly interface, allows users to efficiently manage inventories at multiple locations and streamline order processing. The technologies utilized for ensuring data entry accuracy and enhancing accessibility are barcode scanning and cloud computing. This project demonstrates IMS's capabilities to change inventory management practices by offering savings and reducing turnaround time, which improves customer satisfaction, as elaborated in the paper. The author ends with views on the implementation and future improvement for scalability and integration with other business systems. This paper presents a system design and implementation aimed at enhancing the efficiency of inventory tracking, sales management, and financial transactions. The system encompasses customer information management, real-time stock updates, sales tracking, and payment management. It provides a seamless experience to customers and administrators alike. The system minimizes errors and ensures accurate data flow and decision-making based on detailed reports and automated alerts with an interlinked database for customer, product, sales, and payment information system. The expected benefits include increased operational efficiency, improved inventory management, streamlined transaction processes, thus improving customer satisfaction and effective use of business resources.